Mapping for Tracking Sexually Transmitted Infections by Subdistricts in Surabaya, Indonesia - Susilaningrum, Destri; Ulama, Brodjol Sutijo Suprih; Hibatullah, Fausania; Anjani, Diandra Soja (UI Scholars Hub, 2024)
The 2014 shutdown localization of prostitution in Surabaya City, East Java Province, Indonesia, has given rise to an illegal prostitution industry, resulting in the spread of uncontrolled sexually transmitted infections (STIs). Mapping needs to be done to track the spread of the disease. This study used secondary data on STIs in 2020 from the Surabaya City Health Office. By using biplot analysis, this study sought to offer a detailed understanding of the distribution and dynamics of STI cases in different parts of Surabaya. The early-stage syphilis was found in Tegalsari and Krembangan Subdistricts; then, gonorrheal urethritis was found in Tandes, Karang Pilang, and Pabean Cantian Subdistricts. Meanwhile, gonorrhea was typically found in Tandes, Gunung Anyar, Sawahan, and Karang Pilang Subdistricts. On the other hand, Tegalsari, Krembangan, and Pabean Cantian Subdistricts also had cases of advanced syphilis. This study enables relevant parties, specifically the Surabaya City Health Office, to monitor the method's rapid spread and respond to each case according to the predominant type of STI.